COUNTING $S_5$-FIELDS WITH A POWER SAVING ERROR TERM. (1st May 2014) - SHANKAR, ARUL; TSIMERMAN, JACOB
Abstract: We show how the Selberg $Λ ^2$ -sieve can be used to obtain power saving error terms in a wide class of counting problems which are tackled using the geometry of numbers. Specifically, we give such an error term for the counting function of $S_5$ -quintic fields.